Antibiotics as a silent driver of climate change? A case study investigating methane production in freshwater sediments - E. Bollinger (Elsevier, 2021)
Methane (CH4) is the second most important greenhouse gas after carbon dioxide (CO2) and is inter alia produced in natural freshwater ecosystems. Given the rise in CH4 emissions from natural sources, researchers are investigating environmental factors and climate change feedbacks to explain this increment. Despite being omnipresent in freshwaters, knowledge on the influence of chemical stressors of anthropogenic origin (e.g., antibiotics) on methanogenesis is lacking. To address this knowledge gap, we incubated freshwater sediment under anaerobic conditions with a mixture of five antibiotics at four levels (from 0 to 5000 µg/L) for 42 days. Weekly measurements of CH4 and CO2 in the headspace, as well as their compound-specific δ13C, showed that the CH4 production rate was increased by up to 94% at 5000 µg/L and up to 29% at field-relevant concentrations (i.e., 50 µg/L). Metabarcoding of the archaeal and eubacterial 16S rRNA gene showed that effects of antibiotics on bacterial community level (i.e., species composition) may partially explain the observed differences in CH4 production rates. Despite the complications of transferring experimental CH4 production rates to realistic field conditions, the study indicated that chemical stressors contribute to the emissions of greenhouse gases by affecting the methanogenesis in freshwaters.